Bank Employees’ Fatigue Level in Relation to Office Lighting - Zahoor, Asma; Abiodullah, Muhammad; Siddiqi, Anis Ahmad (Nurture, 2018)
This research is focused to study light’s visual and non visual impact. The objectives of research are to study lighting systems of banks’ buildings in selected areas of Lahore, Pakistan. Lighting system is studied in term of light level, light color, shadows reflections and direction etc. In second phase employees’ fatigue level is calculated on a scale and studied its association with their office lighting Light impact on male and female employees were also studied. Forty five branches of nine commercial banks were selected as study sampling. Lighting conditions were assessed through check list and employees’ opinion was also recorder through questionnaire. FACES (Fatigue Adjective Scale; reliability .8) was used to asses employees’ fatigue level. Data Analysis showed significant association between fatigue level and light level (lux level). Fatigue level is also associated with employees age.